Ilmuan Wanita dan Diskursus Sains (Ilmu Pengetahuan) - Suryadilaga, Muhammad Alfatih (Musawa Jurnal Studi Gender dan Islam, 2007)
According to current research, the European commission reports that this year the number of women who receive a PhD (doctorate) reaches 40% or even more for "life sciences", but only 15% of European industrial researchers are women. Especially in Latin America 60% of technological doctors are women, and 59% are in Argentina. However, women aren't playing a significant role in scientific decisions. For example in 1998 at the National Science Foundation Board in the US, only 8 out of 24 of its members are women or 33.3%. Thereby the profile of women must actually still be supported in the context of progressing science that they deserve. Other than focusing on discussing the discourses of science by looking at the origins and the development that until now has produced the Islamic golden age, this article will also give in,depth informationon a few female scientists that has given the world a gift in its struggle to respond to science in the present day. This is not meant to dream of past glory but to sober-up the Moslem men and women to help each other in thinking of the importance of science and as soon as possible watch the development of science and technology right now!